KOMUNIKASI PEMBANGUNAN PEMERINTAH ACEH BARAT DALAM PEMBERDAYAAN PEREMPUAN MELALUI PENGOLAHAN ECENG GONDOK - Desi Maulida; Safrida Safrida; Salma Salma; Saiful Amri (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2022)
Community empowerment is an effort to make people empowered and independent. Communication has an important role in the context of development and social change. Communication in empowerment is directed at raising the motivation and potential of every member of the community to rise up and be empowered to change their lives for the better. The purpose of this study is to examine and analyze development communication strategies carried out by the West Aceh District Government, especially Arongan Lambalek District. The research method used is descriptive qualitative, with data collection techniques namely observation, interviews and documentation. The results showed that there were three development communication strategies carried out by the local government in realizing women's empowerment from the processing of water hyacinth plants, including choosing the right media such as social media (facebook, instagram, youtube), through events or exhibitions of MSME products. Furthermore, conducting instructional design through socialization and special training to hone the potential and creativity of women in producing quality water hyacinth products. The last strategy is to seek community participation, this is aimed at embracing every woman so that she can earn independently from the sales of products.